Study on the Trend in Microbial Changes during the Fermentation of Black Tea and Its Effect on the Quality - Changwei Liu; Haiyan Lin; Kuofei Wang; Zhixu Zhang; Jianan Huang; Zhonghua Liu (Foods, 2023)
The role of tea endophytes in black tea fermentation and their impact on black tea quality remain unclear. We collected fresh leaves of Bixiangzao and Mingfeng tea and processed them into black tea, while testing the biochemical composition of both the fresh leaves and the black tea. We also used high-throughput techniques, such as 16S rRNA, to analyze the dynamic changes in the microbial community structure and function during black tea processing in order to investigate the influence of dominant microorganisms on the quality of black tea formation. Our results showed that bacteria, such as Chryseobacterium and Sphingomonas, and Pleosporales fungi dominated the entire black tea fermentation process. Predicted functional analysis of the bacterial community indicated that glycolysis-related enzymes, pyruvate dehydrogenase, and tricarboxylic acid cycle-related enzymes were significantly elevated during the fermentation stage. Amino acids, soluble sugars, and tea pigment content also increased considerably during fermentation. Pearson’s correlation analysis revealed that the relative bacterial abundance was closely related to the content of tea polyphenols and catechins. This study provides new insights into the changes in microbial communities during the fermentation of black tea and demonstrates understanding of the basic functional microorganisms involved in black tea processing.